Immunoreactive determinants of CA 125 in women with endometriosis. Issue 12 (December 1989) - Mojiminiyi, O A; Bramwell, M E; Kennedy, S H; Shepstone, B J; Humm, S M; Barlow, D H
Abstract : Among 10 patients with endometriosis CA 125 was increased (greater than 35 U/ml) in endometriotic cyst fluid in all the patients, but only two had increased serum concentrations. Gel electrophoresis of serum, endometriotic cyst fluid, and endometriotic tissue resolved the CA 125 immunoreactive fragments from the three sources into bands of similar electrophoretic mobilities. Electrophoresis under reducing and non-reducing conditions showed immunoreactive fragments of apparent masses of 55, 000 and 140, 000 daltons, respectively. Analysis under reducing conditions did not result in loss of activity. CA 125 antigen is thought to be a high molecular weight glycoprotein complex. As far as is known, this is the first report describing lower molecular weight immunoreactive determinants of CA 125.